PENGARUH KOMITMEN DAN KREATIVITAS KERJA KEPALA MADRASAH TERHADAP KINERJA GURU DI MADRASAH ALIYAH NEGERI 3 BATANG HARI - Julia Fitri; Muhammad Yusup; Zilawati Zilawati (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to describe, test, and analyze the influence of commitment and the headmaster’s work creativity on teacher performance at Madrasah Aliyah Negeri 3 Batang Hari. This study uses a quantitative research method with a survey design that uses questionnaires as a data collection tool. Data analysis uses multiple regression analysis with the help of the Statistical Package for the Social Sciences (SPSS) program. Based on the research results obtained, it can be concluded that commitment has a significant influence on teacher performance, namely t_{count} > t_{table} or 2.571 > 1.724. The headmaster’s work creativity has a significant influence on teacher performance, namely t_{count} > t_{table} or 2.131 > 1.724. The results of the regression coefficient test show that the commitment and work creativity of the headmaster influence teacher performance at Madrasah Aliyah Negeri 3 Batang Hari. The percentage contribution of the independent variable X_1 (Commitment) is 54.3% and X_2 (Headmaster’s Work Creativity) is 45.0% toward the dependent variable Y (Teacher Performance), while the remaining 2.1% is influenced or explained by other variables. The conclusion of this study is that Teacher Performance at Madrasah Aliyah Negeri 3 Batang Hari is influenced by the variables of Commitment and Headmaster’s Work Creativity.